Conceptions about teaching, learning, theater and practice in university teachers of the Bachelor of Performing Arts at the Antonio Nariño University (Papeles, 2020)
This research revolves around the concepts of teaching, learning and theater in three teachers of the Bachelor of Performing Arts at the Antonio Nariño University located in Bogotá, Colombia. Given that there are few investigations on the subject with teachers of this discipline, the need arises to deepen and build new references that contribute to this field of study. In this sense, an analysis is made of the conceptions and practices of the teachers involved. The research is qualitative and the data treatment is carried out by means of the frequency analysis produced by the coding carried out. It is concluded that a theoretical and practical wealth is evidenced in front of the analyzed variables, teaching, learning and theater, however, more structured knowledge on the discipline is identified than on the other two questions investigated.
Keywords: Conceptions; Artistic Education; Teacher Training; Theatre; Theatrical Teaching; Theatrical Learning